Entrepreneurial Dynamics and Typology in Rural Development - Setiyo Yuli Handono; Kliwon Hidayat; Mangku Purnomo; Hery Toiba (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
The term “rural entrepreneurs (RE)” has become a social and rural development factor in developing countries, particularly Indonesia. This research aimed to analyze the dynamics of rural entrepreneurship and describe the typology of entrepreneurship. This research was conducted in three typologies of villages, such as (1) agricultural industry, (2) agritourism, and (3) traditional area, in Malang Regency, East Java, Indonesia. Data were collected through village observation, in-depth interviews with 90 informants, and Focus Group Discussions (FGDs). The dynamics of rural entrepreneurship were affected by various factors: (a) politics, (b) social networks, and (c) economics. Furthermore, three typologies of RE were identified: (1) political-based RE, (2) economic asset-based RE, and (3) social network-based RE. Meanwhile, entrepreneurs could accumulate rural resources, comprising local government and social-economic networks. In summary, the primary keys to encouraging social development in rural areas were providing access to economic assets and social networks and boosting entrepreneurial spirit.